Persepsi Siswa tentang Kegiatan Rohani Islam (Rohis) dan Kontribusinya terhadap Pembentukan Karakter di SMP Negeri 26 Surabaya - Dhekis Baskoro Aji; Junaedi Junaedi; Abdul Muqit (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The increasing prevalence of bullying and moral degradation among students necessitates schools to strengthen character education through effective approaches. This study aims to analyze student perceptions of Islamic Spiritual extracurricular activities (Rohis) and their contribution to character building at SMP Negeri 26 Surabaya. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews and open-ended questionnaires administered to Rohis members and supervising teachers. The findings reveal an interesting dynamic in perception: students tend to interpret Rohis through operational tasks (such as maintaining mosque order and arranging prayer rows), while teachers emphasize the aspect of moral cultivation. Nevertheless, both perspectives converge on the conclusion that structured Rohis activities (daily, weekly, and annual) are effective in shaping student character. The character values developed include religious discipline, responsibility, politeness, and self-confidence. The study concludes that Rohis serves not merely as a gathering place but as a crucial medium for habituation in internalizing Islamic values and preventing deviant behavior within the school environment. Keywords: Rohis, Character Education, Student Perception, Religious Character, SMP Negeri 26 Surabaya.